Folha-diagnóstica e faixa crítica de nutrientes em folhas de cajueiro-anão - Martins, Thais da Silva (2019)
Foliar diagnosis is one of the methods used to evaluate the perennial plants nutritional status, however, for cashew crop, the use of this technique is still incipient. There is no indication of which leaf to sample, and there is no table for the interpretation of nutrient contents in dwarf cashew leaves. The objective of this study was to define the index leaf and the critical nutrient range in dwarf cashew genotypes leaves. Leaf samples were collected in a cashew orchard planted in 2011, with four clones: ‘CCP 76’, ‘BRS 189’, ‘BRS 226’ and ‘BRS 265’. Leaf samples were collected in 2015, 2016, 2017 and 2018, with 10 plants per line at the beginning of the flowering season (June/August). In each plant, leaves from four branches with inflorescence were collected, at the north, south, east and west positions, at a mean plant height (≈ 1.60 m). The first until the sixth fully expanded leaf was collected, from the inflorescence towards the base of the branch. After collection, the leaves were washed, dried in a forced air circulation oven, and then ground and stored. Then, the total macro and micronutrients and sodium contents were determined in the samples. The experimental design was a randomized complete block design, with the cashew clones in the main plot, the leaves positions on the branches in the subplots and four replications. P, K, Ca, Mg, Mn and Zn contents were influenced by the interaction between the clones and the leaf position in the dwarf cashew branch. ‘BRS 189’ and ‘BRS 265’ presented, for most nutrients and sodium, the highest and lowest contents in the dwarf cashew leaves, respectively. In general, the 5th and 6th leaves of the branch present the highest nutrients and sodium contents and the lowest coefficients of variation and can therefore be indicated as index leaf for the evaluation of the dwarf cashew nutritional state. Differences in the nutrient content in the leaves of four clones of dwarf cashew allows to obtain the critical nutrient range specific for each genotype.